Developing Countries, Dispute Settlement, and the Advisory Centre on WTO Law - Bown, Chad P. (2012)
Critical appraisals of the current and potential benefits from developing country engagement in the WTO focus mainly on the Doha Round of negotiations. This paper examines a different aspect of developing country participation in the WTO: use of the WTO dispute settlement system to enforce foreign market access rights already negotiated in earlier rounds of multilateral negotiations. We examine data on developing country use from 1995 through 2008 of the WTO Dispute Settlement Understanding (DSU) to enforce foreign market access. The data reveal three notable trends: developing countries' sustained rate of self-enforcement actions despite declining use of the DSU by developed countries, developing countries' increased use of the DSU to self-enforce their access to the markets of developing as well as developed countries, and the prevalence of disputes targeting highly observable causes of lost foreign market access, such as antidumping, countervailing duties, and safeguards. The paper also examines how introduction of the Advisory Centre on WTO Law (ACWL) into the WTO system in 2001 has affected developing countries' use of the DSU to self-enforce their foreign market access rights. A first pass at the data indicates that developing country use of the ACWL mirrors their use of the DSU more broadly; the ACWL has had little effect in terms of introducing new countries to DSU self-enforcement. A closer look at the data reveals evidence on at least three channels through which the ACWL may be enhancing developing countries' ability to self-enforce foreign market access: increased initiation of sole-complainant cases, more extensive pursuit of the DSU legal process for any given case, and initiation of disputes over smaller values of lost trade.